Odpowiedzi

2010-01-04T17:33:47+01:00
A)
3x+y=5 |*(-2)
2x-y=0 |*3
-6x+2y=10
6x-3y=0
dodajemy
-y=10 |:(-1)
y=-10
x= 5
b)
2x-y=5
x+y=4 |*(-2)
2x-y=5
-2x-y=4
dodajemy
-2y=9 |:(-2)
y=4,5
x=4,75
c)
-x-y=-6
-x+y=2
dodajemy
-2x=-4 |:-2
x=2
y=-4
d)
4x-5y=-4
-2x+3y=1,1 |*2
4x-5y=-4
-4x+6y=2,2
dodajemy
y=-1,8
x=1,25
e)
-2x+y=0 |*3
3x-3y=1
-6x+3y=0
3x-3y=1
dodajemy
-3x=1 |:-3
x= -1/3
f)
3x-2y=-12 |*-2
2x-5y=-19 |*3
-6x+4y = 24
6x-15y=-57
dodajemy
-11y=-33 |:-11
y=3
x=-2

2010-01-04T17:37:30+01:00
A)
{3x+y=5
{2x-y=0

5x=5 /:5
x=1
3+y=5
3+2=5
x=1
y=2


b)
{2x-y=5
{x+y=4

3x=9/:3
x=3
6-y=5
6-1=5
x=3
y=1

c)
{-x-y=-6
{-x+y=2
-2x=-4/:(-2)
x=2
2-y=-6
2-8=-6
x=2
y=8

d)
{4x-5y=-4
{-2x+3y=1,1/x2

{4x-5y=-4
{-4x+6y=2,2
y=-1,8

4x-5(-1,8)=-4
4x-9=-4
4x=9-4
4x=5/:4
x=1,25

x=-1,8
y=1,25

e)
{-2x+y=0/x3
{3x-3y=1

-6x+3y=0
3x-3y=1

3x=1/:3
x=1/3

3 x 1/3-3y=1
1-3y=1
3y=1-1
3y=0/3
y=0

x=1/3
y=0

f)
{3x-2y=-12/x2
{2x-5y=-19/x(-3)

6x-4y=-24
-6x+15y=57

11y=33/11
y=3

2x-15=-19
2x=-19-15

2x=-34/2
x=-17

x=-17
y=3